Eksistensi dan Kehujjahan Urf sebagai Sumber Istimbath Hukum - Lailita Fitriani; Luthfa Surya Anditya; Minahus Saniyyah; Nicken Nawang Sari; Iffatin Nur (Universitas Muhammadiyah Surabaya, 2021)
Abstract The science of Usul Fiqh developed along with the development of Islam to various areas in the Arabian Peninsula. Research by the Usul Fiqh, it is necessary because many cultures outside of the Arabian Peninsula, which are at odds with the local culture of the Arabian Peninsula. Of course, it is a requirement of local communities who do not know much about Islam. Therefore, the clergy continue to do a lot of efforts to resolve the various problems that exist. Where it is constituted by several methods for the formulation of Islamic law in addition to the